Shaping values in knowledge sharing technology: investigating the Islamic concept of niyyah (intention) in developing knowledge-based systems in Malaysian political organization - Saidin, Aznan Zuhid (2012)
Knowledge sharing technology, similar to other forms of technologies, is created not without a purpose. It strives to improve the sharing and dissemination of knowledge in an organization, but nevertheless undesirable outcomes do occur. For a widely applicable technology like this, the effects would be far reaching. These effects may originate from misuse of the user; however the technology would also be a contributing factor. Those affected would question why such a technology was developed, and a considerable part of the answer lies with the developer of the technology. Values and ethics of the ICT professional responsible for developing the system would shape the reason for creating a certain technology or application. Therefore, the focus would be on the intention of the developer which eventually would have bearings on the technology. Special attention is given to knowledge-based systems in Malaysian political organization as a case study. In viewing ethical practices from the Islamic standpoint, the concept of niyyah (intention) plays an important role in providing direction for actions of man, which would also include the development of knowledge sharing technology. This paper will investigate based on the Sunnah (Prophetic tradition) describing this concept. Studies and elaborations of the Muslim scholars on this Sunnah will be discussed. From this investigation, it is anticipated that positive values of the professional in setting the direction for technology development would in due course shape values for the positive evaluation of knowledge sharing systems in political organizations.